Assessing EU Leadership in Inter-regional Relations The Case of the Institutionalisation of ASEAN Disaster Management - Tercovich, Giulia (Taylor & Francis, 2022)
This book comparatively analyses the role of the EU in influencing the policies of other regional organisations by assessing its role in leading the institutionalisation of ASEAN disaster management institutions.